Relationship between C-Reactive Protein Levels, Lactate Dehydrogenase, and Neutrophil-to-Lymphocyte Ratio with Coronavirus Disease 2019 Severity - Hendra Wana Nur'amin; I Nyoman Suarjana; Mohammad Rudiansyah; Nanang Miftah Fajari; Djallalluddin Djallalluddin (Berkala Kedokteran, 2023)
Abstract: Risk stratification of Coronavirus disease 2019 (COVID-19) patients is very important to determine patient care and prognosis. The reliable parameters include C-reactive protein (CRP), lactate dehydrogenase (LDH), and neutrophil-lymphocyte ratio (NLR). This study aimed to determine the relationship between CRP, LDH, and NLR levels with the severity of COVID-19 patients. An observational study with a cross-sectional approach was conducted at Ulin Hospital Banjarmasin on 91 eligible subjects. A logistic regression test was conducted to determine the relationship between variables and the severity of COVID-19. The results showed that there was no significant relationship between CRP levels and the severity of COVID-19 (prevalence odds ratio (POR) 0.85, 95% confidence interval (CI 95%) 0.34-2.09, p=0.72). There was a significant difference between the mean LDH levels in severe COVID-19 compared to non-severe COVID-19 (1006 + 601.77 vs 543.5 + 480.41, p<0.001), with POR 4.23, 95% CI 95% 1.56-11.45, p=0.005; there was also a significant difference between the mean NLR values in severe COVID-19 compared to non-severe COVID-19 (9.01 + 6.32 vs 5.38 + 5.03, p=0.002) with POR of 12.21 CI 95% 3.80-39.31, p<0.001. This study showed that LDH levels and NLR values were important predictors of COVID-19 severity.